O Banquete de Platão e a gênese da noção de tradição - Elsa Buadas (O Que Nos Faz Pensar)
What is presented here as an article corresponds to a chapter of my doctoral thesis entitled “Metaphysics as Onto-theo-logy: an interpretation of Plato’s philosophy in the light of Martin Heidegger’s thought”. This chapter is dedicated to Plato’s Symposium where, according to my opinion, the genesis of the concept of tradition takes place: the idea of ​​safeguarding what must be remembered and bequeathed to posterity, a safeguard that will draw a guiding thread, reconnecting each present generation to future generations. The text proceeds to a comparative analysis of the understanding of eros in the Symposium and in the Phaedrus, after an exposition of the two Socratic participations in the Symposium –the Socrates/Agaton dialogue and the Socrates/Diotima dialogue. The starting point of this comparison is the verification of a radical difference between the two: while in the dialogue Phaedrus the doctrine of the immortality of the soul is emphatically defended, in the Symposium there are no traces of this doctrine, since here men are recognized, just as throughout the Greek mytho-poetic tradition, as “the mortals”. This radical difference, in my opinion, outlines two different civilizing projects, projects that, in their most general features, anticipate the two great constellations of the Western tradition: classical metaphysics realized as Christian theology on the one hand, and modern metaphysics with its notion of secular progress that will lead to the Nietzschean will to power, understood as “will to will”, on the other hand. The first project anticipates the notion of paradise in the promise of an eternal life blessed in the coexistence with the gods, whose winged souls would share